Usefulness of a personalized algorithm‐based discharge checklist in patients hospitalized for acute heart failure - Florent Allain; Virginie Loizeau; Laure Chaufourier; Maya Hallouche; Laurence Herrou; Amir Hodzic; Katrien Blanchart; Annette Belin; Alain Manrique; Paul Milliez; Rémi Sabatier; Damien Legallois (ESC Heart Failure)
Abstract Aims The aim of this study is to evaluate the usefulness of a personalized discharge checklist (PCL) based on simple baseline characteristics on mortality, readmission for heart failure (HF), and quality of care in patients hospitalized for acute HF. Methods and results We designed an algorithm to generate PCL, based on 2016 HF European Society of Cardiology Guidelines and the screening of common comorbidities in elderly HF patients. We prospectively included 139 patients hospitalized for HF from May 2018 to October 2018. A PCL was fulfilled for each patient at admission and 24 to 48 hours before the planned discharge. A control cohort of 182 consecutive patients was retrospectively included from May 2017 to October 2017. The primary composite endpoint was mortality or readmission for HF at 6 months. The secondary endpoints were mortality, readmission for HF, and quality of care (evidence‐based medications, management of HF comorbidities, and planned care plan). There was no difference among baseline characteristics between PCL and control cohorts; mean age was 78.1 ± 12.2 vs. 79.0 ± 12.5 years old (P = 0.46) and 61 patients (43.9%) vs. 63 (34.6%) had HF with left ventricular ejection fraction (LVEF) <40% (P = 0.24). During the 6 month follow‐up period, 59 patients (42.4%) reached the primary endpoint in the PCL cohort vs. 92 patients (50.5%) in the control cohort [hazard ratio (HR): 0.79, 95% confidence interval (CI) (0.57–1.09), P = 0.15]. Subgroup analysis including only patients with either altered (<40%) or mid‐range or preserved (≥40%) LVEF showed no significant difference among groups. There was a non‐significant trend toward a reduction in HF readmission rate in the PCL group [38 patients (27.3%) vs. 64 patients (35.2%), HR: 0.73, 95%CI (0.49–1.09), P = 0.13]. There was no difference regarding survival or the use of evidence‐based medications. A higher proportion of patients were screened and treated for iron and vitamin D deficiencies (53.2% vs. 35.7%, P < 0.01 and 73.4% vs. 29.7%, P < 0.01, respectively), as well as malnutrition supplemented in the PCL group. There was a higher referral to HF follow‐up programme in the PCL group but not to telemedicine or cardiac rehabilitation programs. Conclusions In this preliminary study, the use of a PCL did not improve outcomes at 6 months in patients hospitalized for acute HF. There was a non‐significant trend towards a reduction in HF readmission rate in the PCL group. In addition, the management of HF comorbidities was significantly improved by PCL with a better referral to follow‐up programme. A multicentre study is warranted to assess the usefulness of a simple costless personalized checklist in a large HF patients' population.